Moonshots and the New Industrial Policy Questioning the Mission Economy - Henrekson, Magnus; Sandström, Christian; Stenkula, Mikael (International Studies in Entrepreneurship,, 2024)
This open access book raises some central questions: Do we need moonshot policies to spur innovation and economic growth? What are the risks associated with such policies? Economic turbulence, the COVID-19 pandemic, and mounting environmental concerns have paved the way for a renaissance of targeted industrial policy. In particular, the idea that society should be organized around large missions is gaining momentum among high-income economies. However, the authors and editors of this volume contend that this shift has occurred without much critical examination, especially as the European Union has adopted these ideas, and Western economies are now increasingly organizing toward the achievement of large, state-formulated goals. Recognizing the urgent need for continued scholarly attention to question notions of the mission economy, more than 20 scholars discuss the dangers of top-down/vertical approaches to industrial policy and draw attention to the progress of independent enterprise, entrepreneurialism, and market solutions in a sound economy and society. By critically examining mission-oriented innovation policies, using theoretical perspectives and empirical investigations, the book highlights both the mechanisms behind failed missions and alternative approaches. This is a must-read for policy researchers and policymakers alike.